Towards the convergence of integration processes in South America - Chiri Márquez, Renzo (2018)
This paper analyzes the current estate of the diverse integration processes in South America; their different orientations and emphasis, their common denominators and divergences, but mainly, their necessity to impulse efforts and synergies searching for their convergence in a great sub regional integration project. The institutional convergence of the diverse integration processes set in motion in South America, may serve as an efficient instrument to achieve greater levels of economic and social well-being, deepening and improvement of the regional democratic standards and forge a geopolitical block that allows us to transform South America in to an international actor that takes advantage and manages the opportunities generated by globalization better.